Moral Degradation and Exploitation of Women in Shobha De’s Starry Nights: A Critical Study - Jayant M. Parmar (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2021)
India is a nation where women suffer more than males as a result of the society's contradictory conduct toward women. People are willing to modify women in the name of societal values and morals not just in the villages but also in large metropolitan centers. However, the suffering of women in large urban areas or metropolitan cities differs from that of women in rural areas. Village women suffer more as a result of village residents' continued belief in old harsh social customs whereas urban women suffer from society’s degradation of moral values and physical exploitation. Shobha De tries her hardest to portray the moral degradation and exploitation of women in the film business in her novel, Starry Nights. The present paper is analysis of women’s portrayal specially with reference to urban women in particular.